ADVANTAGES OF STRATEGIC MANAGEMENT ACCOUNTING AS AN INFORMATION AND ANALYTICAL TOOL FOR THE IMPLEMENTATION OF SUSTAINABLE EVELOPMENT STRATEGY - Ushanov, I.G (Хуманитарни Балкански изследвания, 2019)
The practical implementation of the principles of sustainable development, which are now on the agenda of many commercial organizations aimed at long-term value creation, requires, among other things, reforming the accounting and analytical system of the organization. Qualitative development of a sustainable development strategy is impossible without proper information support, and it is essential to obtain relevant information not only about the internal environment of the organization, but also about key aspects of the external environment. Traditional management accounting is not able to fully solve the problem of information support for the implementation of the principles of sustainability, as focused primarily on the internal factors of economic activity of the organization. There is a need to build such an information and analytical system that is able to provide the management of the organization with quality information about environmental factors. In the role of such an accounting and analytical system, it is proposed to consider strategic management accounting, which allows to accumulate information about the environment external to the organization, and to provide a significant increase in the analytical capabilities of management in the development of management decisions aimed at implementing the principles of sustainability and creating business value in the long term. The article discusses the advantages of using various tools of strategic management accounting for information and analytical support of the implementation of the strategy of sustainable development.